2009
DOI: 10.1080/08037050902850184
|View full text |Cite
|
Sign up to set email alerts
|

Increased perfusion pressure enhances the expression of endothelin (ETB) and angiotensin II (AT1, AT2) receptors in rat mesenteric artery smooth muscle cells

Abstract: In the present study, we hypothesized that changes in perfusion pressure result in altered expression of mRNA and protein encoding for the ETA-, ETB-, AT1- and AT2-receptors in rat mesenteric vessels. Segments of the rat mesenteric artery were cannulated with glass micropipettes, pressurized and luminally perfused in a perfusion chamber. After either exposure to no ("organ culture" (0 mmHg)), normal (85/75 mmHg) or high pressure (160/150 mmHg) at constant flow for 1-17 h, the vessel segments were snap frozen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…We hypothesize that the change in vascular wall shear stress and luminal pressure that occur during a stroke or organ culture is one important factor (Olesen et al, 1988). An early study of isolated mesenteric arteries were perfused at different flow levels and perfusion pressures (Szok et al, 2001) showed that perfusion at increased pressure (150 mm Hg) results in enhanced ET B receptor mRNA expression (Lindstedt et al, 2009). This study supports the hypothesis that pressure changes can induce receptor changes.…”
Section: Upstream Initiators Of Cerebrovascular Signal Transduction Amentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that the change in vascular wall shear stress and luminal pressure that occur during a stroke or organ culture is one important factor (Olesen et al, 1988). An early study of isolated mesenteric arteries were perfused at different flow levels and perfusion pressures (Szok et al, 2001) showed that perfusion at increased pressure (150 mm Hg) results in enhanced ET B receptor mRNA expression (Lindstedt et al, 2009). This study supports the hypothesis that pressure changes can induce receptor changes.…”
Section: Upstream Initiators Of Cerebrovascular Signal Transduction Amentioning
confidence: 99%
“…In addition, ET B receptors are elevated in vascular smooth muscle following experimental chronic increases in intraluminal pressure (Lindstedt et al, 2009) and in human hypertension (Nilsson et al, 2008), which is a well-known risk factor for stroke. Thus, a range of stroke risk factors are able to enhance cerebrovascular vasoconstrictor receptor upregulation, and this mechanism may be a target for therapy to minimize stroke risk in certain patients.…”
Section: Upstream Initiators Of Cerebrovascular Signal Transduction Amentioning
confidence: 99%
“…Studies showing increased expression of and vasoconstriction by ET B and AT 1 receptors in arteries following elevated perfusion pressure could point to the latter. Thus, using pressure myography, rabbit carotid and rat mesenteric arteries subjected to high pressure of 160 mm Hg for 6 and 17 h, respectively, showed increased levels of both mRNA and protein for the ET B receptor, compared to normotensive controls at 80-90 mm Hg [17,18]. Elevated pressure also increased AT 1 receptor protein expression in the mesenteric arteries [18].…”
Section: Discussionmentioning
confidence: 99%
“…All experimental models employed to investigate this particular phenomenon to date have included an element of reperfusion. It could be speculated that reperfusion-induced hyperperfusion could be the possible culprit as studies have shown increased ET B receptor-mediated contractile responses and receptor protein expression as well as elevated levels of AT 1 receptor mRNA in response to increased perfusion pressure [17,18,19]. On the other hand, there are also indications of a favouring of ET B receptor-mediated contractions in low-pressure systems such as veins [20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…This is further supported by the fact that activation of the AHR by exogenous ligands sensitizes mice to Ang II-mediated hypertension [36], and induces AT1R mRNA expression in mesenteric arteries (unpublished data). Further, physiological shear stress has been shown to activate the AHR [3739], and to increase AT1R expression [40], providing indirect evidence that AHR may contribute to the regulation of AT1R expression. Additionally, the AHR interacts with several other transcription factors including E2F1, TFIIE, TFIIB, as well as coactivators like CREB-binding protein, CBP/p300 and nuclear receptor-interacting protein 1 (RIP140) [41, 42] and thus alteration in AT1R expression could result from crosstalk with other signaling pathways.…”
Section: Discussionmentioning
confidence: 99%